2022
DOI: 10.1101/2022.06.09.494069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMS-Evoked Responses Are Driven by Recurrent Large-Scale Network Dynamics

Abstract: A major question in systems and cognitive neuroscience is to what extent neurostimulation responses are driven by recurrent activity. This question finds sharp relief in the case of TMS-EEG evoked potentials (TEPs). TEPs are spatiotemporal waveform patterns with characteristic inflections at ∼50ms, ∼100ms, and ∼150-200ms following a single TMS pulse that disperse from, and later reconverge to, the primary stimulated regions. What parts of the TEP are due to recurrent activity? And what light might this shed on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…In addition, Momi, Wang and Griffiths (51) used whole-brain connectome-based computational modelling to reconstruct individual responses to TMS in vitro and highlighted the role of GABAergic neural populations and cortical excitability. Our results align with this previous research (23,24,(49)(50)(51) and support the hypothesis that the complexity of the response following perturbation can be inferred solely based on resting-state activity.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Momi, Wang and Griffiths (51) used whole-brain connectome-based computational modelling to reconstruct individual responses to TMS in vitro and highlighted the role of GABAergic neural populations and cortical excitability. Our results align with this previous research (23,24,(49)(50)(51) and support the hypothesis that the complexity of the response following perturbation can be inferred solely based on resting-state activity.…”
Section: Discussionsupporting
confidence: 92%
“…Along the same lines, a more recent study in humans showed that TMS-EPs can propagate in the network for hundreds of milliseconds, and that such responses highly resemble the EPs generated by delivering ES to the same area 28 . These findings support the notion that TMS responses are not due to peripheral activations, but rather due to recurrent interactions across different regions 29 . Indeed, ES directly excites nearby neurons that cause secondary responses in connected neuronal populations 7,30 .…”
Section: Introductionsupporting
confidence: 87%
“…This study used our recent approach 25 and combined novel analytical techniques and subject-specific mathematical models of brain stimulation. Using combined iES and simultaneous recordings of sEEG and scalp hd-EEG, we mapped the response properties of seven canonical RSNs across 323 stimulation sessions from 36 patients.…”
Section: Introductionmentioning
confidence: 99%